Implementasi Kebijakan dan Tingkat Keberhasilan Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan (Pnpm-Mp) di Kelurahan Bende Kota Kendari - Muhammad Yusuf (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT This study aims to determine the policy implementation of National Program for Urban community Empowerment (PNPM-MP) in order to improve the welfare of the people in the Bendevillage of Kendari city. The method of this research is descriptive qualitative. The object of study isthe Village Office and the district Office as a link in making the transition certificate, the main object is the office of Bende Village as the place of certificate maker. The data and information required in this study were obtained from the people who know and can be trusted (key informant).The techniques of Data collection in this study is in-depth interviews, direct observations at the study site, and documents analysis. The data analysis in this study is a qualitative data analysis. The result showed that the policy implementation was an activity that was executed after the decision guidelines that include partnerships between organizations that aim to inflict the results of mutual reciprocity between citizens and government. Basically, communication is implemented by the government and the community in accordance with the work program directed entirely in the process of policy implementation in PNPM program for urban community at Bende village. Resources implemented by requiring community to be able to implement a policy in accordance with business objectives, the establishment of a working group involving the community to do a job effectively in order to alleviate poverty by well performing. Implementers’ attitudes of PNPM program for urban community that conducted by the community become top priority in improving human resources that able for carrying towards targeted programs in line with working procedure and initiatives in order the people's lives can be improved. Key words: policy implementation, succesfullness, PNPM-MP